2020
DOI: 10.1177/2050312120964138
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategy for elderly patients with the isolated greater trochanteric fracture

Abstract: Background: The objective of this study was to evaluate the risk of femur intertrochanteric fracture associated with femur trochanter major fractures in patients over 65 years of age with magnetic resonance examination for better diagnosis and treatment. Methods: Thirty-one patients who had incomplete femur intertrochanteric fracture diagnosed were included in the study. Patients were classified according to the length of the fracture line crossing the intertrochanteric border. Fracture patterns were described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…By contrast, PFNA results in less trauma, and is more suitable for patients with poor physical conditions and low surgical tolerance. 21,22 Our findings showed that InterTAN and PFNA internal fixation have their own advantages in treating patients with intertrochanteric fracture, which suggesting that when choosing InterTAN and PFNA internal fixation for elderly patients with intertrochanteric fracture, the more beneficial one of the two methods should be rationally selected according to the comprehensive physical examination results of the patients and the patients' wishes. PFNA may be more appropriate for patients who are less tolerant of surgery, whereas InterTAN may be a better choice for patients who are in relatively good health and/or who require greater functional recovery of hip function.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…By contrast, PFNA results in less trauma, and is more suitable for patients with poor physical conditions and low surgical tolerance. 21,22 Our findings showed that InterTAN and PFNA internal fixation have their own advantages in treating patients with intertrochanteric fracture, which suggesting that when choosing InterTAN and PFNA internal fixation for elderly patients with intertrochanteric fracture, the more beneficial one of the two methods should be rationally selected according to the comprehensive physical examination results of the patients and the patients' wishes. PFNA may be more appropriate for patients who are less tolerant of surgery, whereas InterTAN may be a better choice for patients who are in relatively good health and/or who require greater functional recovery of hip function.…”
Section: Discussionmentioning
confidence: 69%
“…By contrast, PFNA results in less trauma, and is more suitable for patients with poor physical conditions and low surgical tolerance. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…The widely adopted protocol suggests that patients should undergo surgery when the fracture line reaches beyond 50% of the longitudinal axis on coronal images [ 4 , 6 , 15 , 16 ]. However, Oc et al [ 17 ] advocated for surgical treatment for all patients, regardless of the spot of intertrochanteric fracture line extension on MRI, or the absence of medical contraindications [ 5 ]. The threshold value for conservative treatment shifted to a fracture line within the lateral two-thirds of the coronal plane, although the rehabilitation schedule varied depending on the site of fracture extension [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…With advancements in medical technology and the introduction and application of Enhanced Recovery After Surgery (ERAS) principles [12], the opportunities for surgical treatment in elderly ITF patients have increased. Currently, surgery is the primary therapeutic approach for this injury [13].…”
Section: Discussionmentioning
confidence: 99%